Characterization and evaluation of the biological control activity of Stenotrophomonas maltophillia against rice blast disease caused by Pyricularia oryzae - Fariman, Azadeh Badri (2020)
Blast is a widespread and damaging disease of cultivated rice caused by the fungus Pyricularia oryzae leading to serious yield losses. Stenotrophomonas maltophilia was shown to produce antimicrobial compounds and has the ability to act as a biological control agent. This study was conducted with three objectives, 1) to isolate, identify and characterise S. maltophilia isolates for in vitro screening against P. oryzae, 2) to identify the antimicrobial compounds produced by selected S. maltophilia isolate, and 3) to determine the efficacy of the selected isolate against P. oryzae and to evaluate the expression of defense-related genes in rice during the pathogen-host interaction in glasshouse trial. Root and rhizosphere samplings were conducted in Selangor, Penang, Perak and Kedah states. The emerged bacteria isolates were identified as S. maltophilia based on morphological method using Xanthomonas maltophiliaselective agar medium and molecular method using polymerase chain reaction (PCR). A total number of 40 colonies were isolated from healthy rice roots and rhizospheres. PCR amplified products were sequenced and compared with related bacteria in the GenBank database. A phylogenetic analysis was conducted using MEGA6 program. Bacteria isolates were confirmed as S. maltophilia and were placed under S. maltophilia cluster. Isolates were subjected to dual culture and culture filtrate tests to determine their antagonistic activities. In dual culture test, eleven isolates showed percent inhibition of radial growth (PIRG) more than 55% and in culture filtrate test, four isolates showed PIRG more than 85%. All four isolates showed the optimum growth temperature of 30-40°C. These four isolates were used for hydrolytic enzymes and secondary metabolites production test in vitro. All of the tested isolates produced protease, chitinase, cellulase, pectinase and lipase. They also produced indole-3-acetic acid (IAA), ammonia and, siderophore. Bioactive compounds produced by S. maltophilia isolate UPMKH2 were identified using Liquid Chromatography-Mass Spectrometry-Mass Spectrometry (LC-MSMS). Two antimicrobial compounds Maculosin and L, L-Cyclo (leucylprolyl) were identified. For in vivo trial, rice plants were inoculated with P. oryzae conidia suspension and S. maltophilia isolate UPMKH2 was applied using both seed treatment and foliar spray. The results showed significant disease suppression, increased plant growth parameters and enhancement of yield-related attributes in plants treated with UPMKH2 in both methods compared to the untreated control with the highest suppression of disease at 55.58 %. Defenserelated gene expression in rice leaf samples with seed treatment application inoculated with P. oryzae was evaluated using RT-qPCR and the result showed that S. maltophilia UPMKH2 was able to increase the expression of target genes, β-1, 3- glucanase (Gns1) and chitinase (Cht-1), compared with the non-treated control. S. maltophilia demonstrated the ability to suppress mycelial growth of P. oryzae with optimal growth at 30-40°C and produced plant growth-promoting compounds in vitro, and high efficacy to reduce blast disease in vivo. Thus, S. maltophilia has great potential to be used as a biological control agent against rice blast disease in the field and also could be a good candidate to address in global warming issue in rice production in the future.